JIMÉNEZ FERNÁNDEZ, C. Y PÉREZ SERRANO, G. (Coords.) (2008). Educación y Género. El conocimiento invisible. Madrid/Valencia, UNED/Tirant lo Blanch. - Mingorance, Pilar (Revista Fuentes, 2016)
JIMÉNEZ FERNÁNDEZ, C. Y PÉREZ SERRANO, G. (Coords.) (2008). Educación y Género. El conocimiento invisible. Madrid/Valencia, UNED/Tirant lo Blanch.